A Note on the Adoption of the Byzantine Models in Medieval Bulgaria (9th–10th Centuries). The Case with the Chrysorrhoas Collection - Miltenov, Yavor (Studia Ceranea, 2017)
The paper aims at examining the first Slavic collection of homilies of John Chrysostom, called Zlatostruy (i.e. Chrysorrhoas or Golden Stream). The peculiarities of its content, compilation strategy and impact on the medieval Bulgarian literature, revealed in previous studies, allow us to extract features that are related to the flourishing of the 10th century Bulgarian literary tradition and the successful adoption of Byzantine models.